Occurrence, Potential Zoonotic Transmission, and Antimicrobial Resistance of Pseudomonas aeruginosa in Cats: A Systematic Literature Review - Lily Roga (Animal Science Study Program, Faculty of Agriculture, Science and Health, Universitas Timor, 2026)
Pseudomonas aeruginosa is an opportunistic Gram-negative pathogen of increasing concern in both human and veterinary medicine due to its intrinsic resistance and ability to acquire multidrug resistance. In companion animals, particularly cats, its clinical relevance is often underestimated despite its association with chronic and difficult-to-treat infections. Moreover, the potential for cross-species transmission and its role within the One Health framework remain insufficiently understood. This study aimed to systematically evaluate the occurrence, potential zoonotic transmission, and antimicrobial resistance patterns of Pseudomonas aeruginosa in cats, as well as their implications for human health. A systematic literature review was conducted following PRISMA guidelines using multiple databases, including PubMed, Scopus, and Web of Science. Relevant studies published between 2012 and 2025 were screened based on predefined inclusion and exclusion criteria. The findings indicate that Pseudomonas aeruginosa is consistently identified in various feline clinical samples, particularly from skin and wound infections, otitis, respiratory tract, and urinary tract. Although not a predominant pathogen, its clinical significance increases in chronic and recurrent cases. Molecular and epidemiological evidence suggests genetic relatedness and shared resistance profiles between animal and human isolates, supporting the possibility of a common reservoir across species. Antimicrobial resistance was widely reported, including resistance to fluoroquinolones, β-lactams, and carbapenems, with the presence of multidrug-resistant (MDR) and extensively drug-resistant (XDR) strains in several studies. In conclusion, cats may act as potential reservoirs of antimicrobial-resistant Pseudomonas aeruginosa, contributing to its circulation at the animal-human interface. These findings highlight the importance of antimicrobial stewardship, infection control, and integrated surveillance strategies within a One Health approach to mitigate the spread of resistant strains.